Anti-predator responses in the Chilean Swallow Tachycineta leucopyga breeding in northwest Patagonia. Issue 1 (2nd January 2019) - Barrionuevo, Melina; Ojeda, Valeria; Dudinszky, Natalie; Ippi, Silvina
ABSTRACT: Capsule: Breeding Chilean Swallows Tachycineta leucopyga in Argentina use visual and acoustic signals in response to potential threats from a predator, but these did not vary with brood age. Aims: To study anti-predator behavioural responses in breeding Chilean Swallows from North Patagonia, Argentina, by using a nest-box experiment. Methods: At days eight and 14 after the first nestlings hatched, Chilean Swallow breeding adults were exposed to a stuffed decoys of either a natural local predator, the Austral Pygmy-Owl Glaucidium nana, or a neutral decoy, a stuffed Rufous-Collared Sparrow Zonotrichia capensis . Results: Anti-predator behavioural responses consisted of displaying dives, circling flights and group mobbing around the predator decoy, together with the emission of several vocalizations, among which a mobbing alarm call was the most frequent. We did not find significant differences in the intensity of parental nest defence behaviours at different nestling ages (8 and 14 days old). Conclusion: Anti-predator behaviour of breeding Chilean Swallows consists of visual and acoustic signals, involving swallows other than the nest owners, and without variation during the nestling period. Our exploratory assessment on the anti-predator behaviour of Chilean Swallows is the first description of the southernmost Neotropical swallow defence behaviour and will therefore help delineate future research.